Réflexions sur un « style ethnique » : la céramique kali’na du littoral oriental des Guyanes - Gérard Collomb (Journal de la Société des Américanistes)
Reflexions about « ethnic style »: Kali’na pottery from the Eastern coast of the Guyanas. Can ceramic styles characterization make it possible to establish a continuity between the archaeological cultures closest to the Contact and the current people on the Eastern coast of the Guyanas? On the basis of a study of potteries made by the Kali’na, which represent today the most significant native population in this zone, this article outlines a brief reply to the question of the « ethnic style ». One can recognize an « ethnic style » through the kali’na potteries ; yet it is less an expression of a closed ethnicity than a result of the interactions and the influences that this group knew before and after the European arrival.